2000
DOI: 10.1063/1.1289393
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of discretization in the direct simulation Monte Carlo

Abstract: We propose a continuous-time formulation of the direct simulation Monte Carlo that allows the evaluation of the transport coefficient dependence on the time step through the use of the Green-Kubo theory. Our results indicate that the error exhibits quadratic dependence on the time step, and that for time steps of the order of one mean free time the error is of the order of 5%. Our predictions for the transport coefficients are in good agreement with numerical experiments. The calculation of the cell size depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(96 citation statements)
references
References 7 publications
5
91
0
Order By: Relevance
“…It should also be noted that our numerical experiments have shown that the numerical error associated with VRDSMC is not strongly affected by other discretization parameters (e.g. Δy) and thus provided ε remains small, much like DSMC [1,13,15], accurate solutions can be obtained with fairly coarse grids and thus total numbers of particles that are not excessively large. Furthermore, this moderate increase in N cell is only practically limiting in applications characterized by Kn 1, while most transition regime flows can be described to engineering accuracy with N cell = O(100), which is not substantially higher than the number of particles per cell required by DSMC.…”
Section: Approximation Error and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be noted that our numerical experiments have shown that the numerical error associated with VRDSMC is not strongly affected by other discretization parameters (e.g. Δy) and thus provided ε remains small, much like DSMC [1,13,15], accurate solutions can be obtained with fairly coarse grids and thus total numbers of particles that are not excessively large. Furthermore, this moderate increase in N cell is only practically limiting in applications characterized by Kn 1, while most transition regime flows can be described to engineering accuracy with N cell = O(100), which is not substantially higher than the number of particles per cell required by DSMC.…”
Section: Approximation Error and Limitationsmentioning
confidence: 99%
“…A convergence proof for this algorithm can be found in [27]; an analysis of the error associated with the timestep discretization can be found in [13,15]. Here, we use a form of the collision integral that is convenient for discussing particle methods [4,5,19].…”
Section: Variance Reduction Using Importance Weights: Vrdsmcmentioning
confidence: 99%
“…The linear dimensions of the cells should be small in comparison with the length scale of the macroscopic §ow gradients normal to the streamwise directions, which means that the cell dimensions should be of the order or smaller than the local mean free path [27,28]. The time step should be chosen to be su©ciently small in comparison with the local mean collision time [29,30]. A very small time step results in an ine©cient advancement of the solution and accumulation of statistics.…”
Section: Free-stream and Flow Conditionsmentioning
confidence: 99%
“…It has been shown [10], [11] that the error in the transport coefficients is proportional to the square of the timestep, with a proportionality constant such that for timesteps of the order of one mean free time the error is of the order of 5%. In our simulations, ∆t < λ/(7c o ), thus making the error negligible.…”
Section: B Simulationsmentioning
confidence: 99%